RETRACTED: Adherence to lifelines diet score and risk factors of metabolic syndrome among overweight and obese adults: A cross-sectional study - Akhavanfar, Roozbeh; Hojati, Ali; Kahrizi, Mohammad Saeed; Farhangi, Mahdieh Abbasalizad; Ardekani, Abnoos Mokhtari (Frontiers in Nutrition, 2022)
Background: An unhealthy diet, sedentary lifestyle, cigarette smoking, and excessive alcohol intake seem to be the most important risk factors for cardiovascular disease and stroke. Many dietary scores have been established to assess compliance with dietary recommendations or eating patterns, but many are not entirely food-based. Lifelines Diet Score (LLDS) was developed in response to current scores' shortcomings, like not being entirely diet-based. In this study, we aimed to see if there were any possible links between total food quality and cardio-metabolic risk factors among adult population. Methods: In the current cross-sectional study, we selected 338 obese individuals aged from 20 and 50 and had a BMI of more than 30 kg/m2. Dietary data were gathered using a validated semi-quantitative food frequency questionnaire (FFQ) that had been tailored for the Iranian population. ELISA kits were used to assess serum glucose, lipids, and insulin levels. In addition, the homeostasis model assessment for insulin resistance index (HOMA-IR) and quantitative insulin sensitivity check index (QUICKI) were calculated. Results: BMI and HC were significantly different (P<0.05) amongst LLDS tertiles, although weight, height, WC, WHR, FM, FFM, BMR, and physical activity levels were not significantly different (P > 0.05). LLDS adherence was associated with lower SBP in patients with high adherence, and a definite inverse connection was seen between different LLDS tertiles and SBP (P = 0.04). TG levels were also significantly lower in the third tertile of LLDS. No significant differences were seen between LLDS tertiles and DBP, TC, HDL-C, LDL-C, glucose, insulin, HOMA-IR, and QUICKI. Conclusion: Our research revealed that individuals with higher diet quality show a reduction in SBP and TG. Further research using experimental and longitudinal methodologies is recommended to understand this relationship better.